Assessing the implementation of total quality management in education administration institutions with special reference to central province sri lanka - Abeykoon, M.W.M.; De Alwis, A.C. (University of Jaffna, 2016)
Purpose of this study was to assess the implementation of TQM aspects among education administration institutions in central province, Sri Lanka. This study focused on identifying the level of Hard TQM implementation and Soft TQM implementation among selected education administration institutions. A five point Likert scale questionnaire was used as the key instrument of data collection. The data were obtained from a survey of 41 administrators in education administration institutions in central province. The findings suggest that the level of hard TQM implementation is at a high level and the level of soft TQM implementation is at a moderate level. Further the study reports that the level of hard TQM implementation is higher than the level of soft TQM implementation. Among the studied Hard TQM techniques Quality Circles is reported as the most adopted technique. Customer/Citizen Satisfaction and Top Management Commitment and Support are the top principles adopted among the studied Soft TQM practices. In addition to that report revealed that there is no significance difference in between districts in central province when implementing hard TQM and soft TQM
Keywords: : Central province; Education administration institutions; Hard TQM, Soft TQM; Total quality management